2023
DOI: 10.3390/foods12163067
|View full text |Cite
|
Sign up to set email alerts
|

Non-Targeted Detection and Quantification of Food Adulteration of High-Quality Stingless Bee Honey (SBH) via a Portable LED-Based Fluorescence Spectroscopy

Abstract: Stingless bee honey (SBH) is rich in phenolic compounds and available in limited quantities. Authentication of SBH is important to protect SBH from adulteration and retain the reputation and sustainability of SBH production. In this research, we use portable LED-based fluorescence spectroscopy to generate and measure the fluorescence intensity of pure SBH and adulterated samples. The spectrometer is equipped with four UV-LED lamps (peaking at 365 nm) as an excitation source. Heterotrigona itama, a popular SBH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
(107 reference statements)
0
2
0
1
Order By: Relevance
“…Así mismo, se puede utilizar un método óptico laser para predecir la posible sustancia utilizada en la adulteración como agua, almidón, solución azucarada, entre otros (El-Raie et al, 2015); además, de que se puede emplear infrarrojo cercano (NIR) (Tan et al, 2021;Raypah et al, 2022a, b), espectroscopía infrarroja por transformada de Fourier (FTIR) (Damto et al, 2023), metabolómica de 1H-NMR no dirigida con quimiometría (Yong et al, 2022), espectroscopía de fluorescencia portátil basada en LED (Suhandy et al, 2023) e inclusive un refractómetro digital de bolsillo (Lyasota et al, 2023), para detectar miel adulterada.…”
Section: Página | 309unclassified
“…Así mismo, se puede utilizar un método óptico laser para predecir la posible sustancia utilizada en la adulteración como agua, almidón, solución azucarada, entre otros (El-Raie et al, 2015); además, de que se puede emplear infrarrojo cercano (NIR) (Tan et al, 2021;Raypah et al, 2022a, b), espectroscopía infrarroja por transformada de Fourier (FTIR) (Damto et al, 2023), metabolómica de 1H-NMR no dirigida con quimiometría (Yong et al, 2022), espectroscopía de fluorescencia portátil basada en LED (Suhandy et al, 2023) e inclusive un refractómetro digital de bolsillo (Lyasota et al, 2023), para detectar miel adulterada.…”
Section: Página | 309unclassified
“…Current methods involve advanced analytical tools coupled with chemometrics [13]. Physicochemical [14][15][16][17], elemental [18], isotopic [19], chromatographic, and hyphenated mass spectrometry methods [20,21], NMR [22,23], DNA-based [24,25], electronic sensing [26,27], and spectroscopic [28][29][30][31][32] techniques are nowadays the most used for predicting botanical and geographical origin, or detecting adulterants [33]. Usually, botanical issues are investigated using chromatographic techniques and physicochemical analyses [12,14,34].…”
Section: Introductionmentioning
confidence: 99%
“…LED-based fluorescence spectroscopy with multiple LED excitation lamps will have a low spectral resolution compared with conventional spectroscopy systems [26][27][28]. On the other hand, Suhandy et al [29] reported an authentication method based on portable and single LED-based fluorescence spectroscopy to assess adulteration in stingless bee honey (SBH). Preliminary laboratory work on the application of LEDbased fluorescence spectroscopy on instant coffee geographic discrimination has been reported [30].…”
Section: Introductionmentioning
confidence: 99%